2001
DOI: 10.1071/mf01214
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity dynamics of female spiny lobster (Panulirus argus) in a south Florida fishery and Dry Tortugas National Park lobster sanctuary

Abstract: Using diver surveys, we compared the size structure, fecundity, and reproductive season of spiny lobsters ( Panulirus argus ) in the Dry Tortugas National Park lobster sanctuary with those of spiny lobsters in the south Florida fishery. The number of lobsters of both sexes larger than the legal size limit declined sharply in the fishery but not in the sanctuary. Clutch sizes were larger in the Dry Tortugas sanctuary, averaging 0.8 million, than in the fishery, averaging 0.3 million. The reproductive season was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 5 publications
2
19
2
2
Order By: Relevance
“…There was little overlap in the size ranges of lobsters older than 2 years in the Florida Keys and dry Tortugas, and to be the same age at these different sizes, lobsters must have grown at different rates at the two locations. Previous studies indicated that the size of lobsters at 50% maturity from the dry Tortugas was considerably larger than that of lobsters from the Florida Keys (davis 1975;Bertelsen & Matthews 2001). our data suggest that lobsters of different sizes at onset of maturity in the dry Tortugas and Florida Keys are likely the same age.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…There was little overlap in the size ranges of lobsters older than 2 years in the Florida Keys and dry Tortugas, and to be the same age at these different sizes, lobsters must have grown at different rates at the two locations. Previous studies indicated that the size of lobsters at 50% maturity from the dry Tortugas was considerably larger than that of lobsters from the Florida Keys (davis 1975;Bertelsen & Matthews 2001). our data suggest that lobsters of different sizes at onset of maturity in the dry Tortugas and Florida Keys are likely the same age.…”
Section: Discussioncontrasting
confidence: 62%
“…lengthfrequency distributions of lobsters show that lobsters from fishing grounds around the Dry Tortugas are significantly larger than lobsters from the Florida Keys fishery (Bertelsen et al 2004). Female spiny lobsters in the Florida Keys with carapace lengths (Cls) as small as 57 mm have been observed carrying eggs, whereas no female less than 70 mm Cl from the dry Tortugas has been observed with eggs (Bertelsen & Matthews 2001). Bertelsen & Matthews (2001) offer several hypotheses for the size-at-maturity differential between the two populations.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bertelsen and Matthews (2001) provide 95th percentile of the CL of females (145 mm) and males (180 mm) captured in the Dry Tortugas National Park in 1996-1998. This park was closed to spiny lobster fishing in 1973 and the data should represent an undisturbed population in Florida (Maxwell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, pulses of larvae arrive at settlement sites in a seemingly unpredictable manner (Eggleston et al 1998;Siegel et al 2008). Dynamic currents in coastal systems (Paris et al 2002) and variability in spawning time over the year, even within species (Bertelsen and Matthews 2001), make quantifying connectivity a challenge. Indeed, in areas with variable currents, asynchronous spawning time can drive speciation (Carson et al 2010).…”
Section: Introductionmentioning
confidence: 99%